2022
DOI: 10.3389/fpsyg.2022.846671
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Investigation of Medical Follow-Up in Long-Term Childhood Cancer Survivors: What Are the Reasons for Non-Attendance?

Abstract: As long-term childhood cancer survivors (CCS) are at risk for late effects, ongoing medical care is crucial to detect and treat physical illnesses as early as possible. However, previous research from around the world has shown that many adult survivors did not participate in long-term medical follow-up. This study aimed to provide insight into German survivors’ care situation, with a particular focus on barriers to follow-up care. We investigated a sample of adult CCS (N = 633) (age M = 34.92; SD = 5.70 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…CCS felt uninformed about how the healthcare system works and how to make it work best for them. This confirms what has been found in qualitative research; young adult CCS often report difficulty navigating the healthcare system, report struggling to coordinate their care due to a lack of knowledge and skills to access care, and lacked information about the purpose of medical follow-up 23,24 . Identifying specific knowledge gaps and increasing interdisciplinary collaboration to reduce the burden on CCS to coordinate their care could improve adherence to follow-up guidelines.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…CCS felt uninformed about how the healthcare system works and how to make it work best for them. This confirms what has been found in qualitative research; young adult CCS often report difficulty navigating the healthcare system, report struggling to coordinate their care due to a lack of knowledge and skills to access care, and lacked information about the purpose of medical follow-up 23,24 . Identifying specific knowledge gaps and increasing interdisciplinary collaboration to reduce the burden on CCS to coordinate their care could improve adherence to follow-up guidelines.…”
Section: Discussionsupporting
confidence: 79%
“…The M age of our sample, 25 years, highlights that these logistical barriers are likely particularly difficult for young adult CCS who are members of the workforce and may have families that depend on them 26,27 . This aligns with prior research in CCS identifying that macro-level barriers, like difficulty booking appointments, is a common barrier to follow-up care, 24,28–30 and with research among young adults with childhood chronic illnesses that experienced transportation concerns and scheduling changes as barriers to transitioning to adult care 31,32 . This study extends these general findings by examining the item-level barriers; we found that CCS reported the lack of after hours and weekend clinic availability and difficulty taking time off work as specific barriers to scheduling appointments for follow-up care.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This may reflect a unique barrier among survivors of AYA and other cancers as cure of the underlying cancer likely contributes to lack of personal knowledge and subsequent misperceptions about risk of adverse late effects of cancer treatment justifying the need for lifelong survivorship care. 68,69 Of equal importance are structural barriers to care, 69 including disparities to access on the basis of income, race/ethnicity, or sex; the direct and indirect costs of care (copayments and health insurance); limited transportation options to the treating institution; and others. 70 Provider-level barriers may also impede successful and seamless transition.…”
Section: Barriers To Transition In Aya Cancer Survivorsmentioning
confidence: 99%
“…This lack of compliance may be multifactorial (e.g., unmet needs of psychological support about fear of recurrence, distance of care facilities from home, lack of information about the importance of follow-up or existing services, motivational aspects, etc. ; Ernst et al, 2022 ), yet numerous issues about the real needs of AYA survivors of childhood and adolescent cancer in the long term have received little attention. The investigation of unmet supportive care needs may serve to demonstrate inadequacies in the support provided by health professionals ( Baudry et al, 2019 ); this exploration therefore seems paramount to fill gaps and adapt existing follow-up care and programs.…”
Section: Introductionmentioning
confidence: 99%